ANALISIS PEMBANGUNAN INFRASTRUKTUR JALAN, LISTRIK DAN AIR TERHADAP INVESTASI DI PROVINSI KALIMANTAN TIMUR - Desi Rahmayanti (2023)
This research is to find out and analyze the delelopment of road infrastructure, electricity and water againts investment in East Kalimantan Province. This study uses data obtained from and is directly related to work studies conducted by the Central Bureau of Statistics and the office of Public works (PU) and (BPS). The data used, namely the lenght of roads, electricity, water, and the amount of foreign investment at the BPS of East Kalimantan Province are used as the basis for analysis from 2012-2021. The result of the study showed that the value of Ftabel (df1 = 2 df2 = 7) was obtained at 4.737414, which means that the value of Fhitung > Ftabel (6.214308 > 4.737414) and probability 0.028534 < 0.05 so it can be concluded that road infrastructure, electricity and water together have an influence on investment. The R-squared value is 0.756522 which means the dependent variable (investment) can be described by the independent variables (road infrastructure, electricity and water) of 75.65% while the remaining 24.35% investment is explained by other variables outside the research. The adjusted R-squared value is 0.63.48% explained by the independent variables (road infrastructure, electricity and water) where the remaining 36.52% investment is described by other variables or other reasons outside the research.